Comparative analysis of synovectomy and total knee replacement in knee joint synovial chondromatosis: A case series - Primaputra, Muhammad RA.; Malau, Vino D.; Budhy, Filberto; Yudhistira, Pramudito (Narra Sains Indonesia, 2024)
Synovial chondromatosis is a rare disorder characterized by cartilaginous growths within the joint lining, often confused with conditions like pigmented villonodular synovitis and rheumatoid arthritis. Primary treatment typically involves surgical synovectomy to remove the affected tissue and loose bodies. Documented cases are limited globally. The aim of this study was to present a case series of synovial chondromatosis and evaluate the functional outcomes by assessing the post-surgical Musculoskeletal Tumor Society (MSTS) score following different surgical interventions (synovectomy alone versus synovectomy with total knee replacement) in a resource-limited setting. Four cases of synovial chondromatosis were reported. A 61-year-old woman with a soft tissue tumor underwent synovectomy and total knee replacement on the right knee, then experienced a periprosthetic infection requiring revision arthroplasty, resulting in an MSTS score of 24. Another case was a 48-year-old woman who had a synovectomy for a lump on the right knee, also achieving an MSTS score of 24. Two additional cases involved women in their mid-to-late 60s who underwent synovectomy for knee lumps, with post-operative MSTS scores of 21 and 19, respectively. This case series underscores the diagnostic and management challenges of synovial chondromatosis in the knee joint, demonstrating various surgical interventions. This case series also suggested that the post-operative MSTS scores were slightly higher (indicating better outcomes) for synovectomy alone compared to synovectomy with total knee replacement, highlighting the need for further research to determine the most effective treatment approach.